Low level laser therapy as management of recurrent aphthous stomatitis: A report of two cases - Rahmayanti, Febrina; Idris, Mohamad Z.; Wimardhani, Yuniardini S.; Indrastiti, Ratna K. (Journal of Case Reports in Dental Medicine, 2023)
Objectives: This report describes 2 cases diagnosed with minor RAS treated with LLLT to relieve pain and promote the healing of the ulcers.Methods: A 21-years old female presented of ulcer on labial mucosa for about 4 days with VAS=5. The ulcer always appears 1-2/month before or on her menstruation period. A 21-years-old female presented of ulcer on right buccal mucosa for about 2 days with VAS=8. The ulcer always appears once a month. The predisposing factor in this case were trauma and stress.Results: We treat the patient with LLLT and educated the patients for management the predisposing factor. After treatment with laser, the pain decreased immediately. The lesions healed completely within 4-5 days and scoring of the Ulcer Severity Scores (USS) also decreased.Conclusion: Low level laser therapy is recommended for patients with minor RAS since it can relieve pain, reduce the healing period and lesion size and recurrence of the lesions.